Efektivitas Kejaksaan Dalam Penanganan Perkara Tindak Pidana Korupsi di Maluku Sebagai Wilayah Kepulauan - Renfan, Nur Hayati (MATAKAO Corruption Law Review, 2023)
Introduction: Based on the Prosecutor's Law number 16 of 2004, especially in Article 30 paragraph 1 letter d it states "in the criminal field the Prosecutor's Office has the duty and authority to conduct investigations into Certain Criminal Laws”. From this it is known that one particular case is a criminal act of corruption. Moreover, taking into account that Maluku is an archipelago, of course there are problems in implementation, which of course are experienced by every District Attorney's Office. Purposes of the Research: This study aims to find out how the effectiveness of handling corruption cases in Maluku as an archipelago. Methods of the Research: This paper uses empirical juridical research methods. The researchers used a case approach (case approach). Results of the Research: The results of this study shows that the Prosecutor's Office in the Maluku region has not been effective in handling Corruption Crime Cases in the archipelago area because law enforcement and legal justice of the prosecutor's office in the Maluku region which are contained in regulations do not accommodate case handling in the archipelago area, this has an impact on non-compliance with the principle of speedy justice and low cost. Because the central trial for Corruption Crimes must be held in the provincial capital, so this is quite burdensome for each Prosecutor's Office. As for the obstacles to carrying out the effectiveness of legal handling, the authors found that there were six (6) factors, namely budget limitations, difficulty accessing from one island to another, internet network in the archipelago, no regulations governing the handling of corruption in the archipelago, difficulties confiscating goods, and the Corruption Court located in Ambon City.